Utilization of biodegradable polymeric materials as delivery agents in dermatology - Rancan F; Blume-Peytavi U; Vogt A (Dove Medical Press, 2014)
Fiorenza Rancan, Ulrike Blume-Peytavi, Annika VogtClinical Research Center for Hair and Skin Science, Department of Dermatology and Allergy, Charité – Universitätsmedizin Berlin, GermanyAbstract: Biodegradable polymeric materials are ideal carrier systems for biomedical applications. Features like controlled and sustained delivery, improved drug pharmacokinetics, reduced side effects and safe degradation make the use of these materials very attractive in a lot of medical fields, with dermatology included. A number of studies have shown that particle-based formulations can improve the skin penetration of topically applied drugs. However, for a successful translation of these promising results into a clinical application, a more rational approach is needed to take into account the different properties of diseased skin and the fate of these polymeric materials after topical application. In fact, each pathological skin condition poses different challenges and the way diseased skin interacts with polymeric carriers might be markedly different to that of healthy skin. In most inflammatory skin conditions, the skin's barrier is impaired and the local immune system is activated. A better understanding of such mechanisms has the potential to improve the efficacy of carrier-based dermatotherapy. Such knowledge would allow the informed choice of the type of polymeric carrier depending on the skin condition to be treated, the type of drug to be loaded, and the desired release kinetics. Furthermore, a better control of polymer degradation and release properties in accordance with the skin environment would improve the safety and the selectivity of drug release. This review aims at summarizing the current knowledge on how polymeric delivery systems interact with healthy and diseased skin, giving an overview of the challenges that different pathological skin conditions pose to the development of safer and more specific dermatotherapies.Keywords: nanocarriers, nanoparticles, biodegradable polymers, skin penetration, hair follicles